Microbiome Differentiation Among Coexisting Nematode Species in Estuarine Microhabitats: A Metagenetic Analysis - Vafeiadou, Anna-Maria; Derycke, Sofie; Rigaux, Annelien; De Meester, Nele; Guden, Rodgee Mae; Moens, Tom (Frontiers in Marine Science, 2022)
Resource partitioning is a mechanism for niche differentiation which can facilitate coexistence of species at local scales. Insights into resource use and niche differentiation of functionally similar and/or taxonomically closely related species are scant, especially so for small organisms that dominate marine sediments in terms of numbers of specimens and species. In this study we characterized the microbiomes of 10 bacterivorous nematode species co-occurring in various estuarine microhabitats using 16S rDNA metabarcoding to address their resource utilization. We investigated microbiome diversity and composition of nematodes collected from six microhabitats in the field: Fucus spiralis, Fucus vesiculosus, fresh and decomposing thalli of Ulva sp., and attached and detached leaves of Spartina anglica. The 10 species belonged to three different families, and included congeneric and morphologically cryptic species. The microbiome of species sharing their microhabitats showed a substantial overlap, suggesting that resource differentiation of species within a microhabitat was rather limited at time of sampling. Microbiomes of the same nematode species found in different microhabitats were also not strongly differentiated. Temporal divergence in resource use may occur, as suggested by temporally divergent microbiome composition of nematodes associated with Ulva sp. The observed high intraspecific variability in microbiome composition of nematodes may be the principal factor explaining the lack of microbiome differentiation among species or microhabitats and may illustrate individual specialization in resource use as a consequence of substantial intraspecific competition.